Point-of-care blood testing with secondary care decision support for frail patients - Novak, A; Cherry, J; Ali, N; Smith, I; Bowen, J; Ray, J; Black, JJ; Cornett, R; Taylor, S; Hayward, G; Lasserson, D (MA Healthcare, 2022)
Aim: A service evaluation was conducted to assess the feasibility and impact of a pilot service to facilitate alternatives to hospital admission for frail patients in supportive care settings. Paramedic assessments were enhanced by point-of-care testing and telephone support from senior physicians. Method: A rapid response vehicle, staffed by a specialist paramedic and equipped with the Abbott i-STAT Wireless 1 point-of-care testing platform that could transmit results to hospital electronic patient record (EPR) systems, was dispatched to frail, non-injured patients over a 3-month period. Results were obtained on scene and transmitted to Oxford University Hospitals EPR system. The patient was then discussed over the telephone with a senior acute medical assessment physician at the Trust for advice and decision support and to coordinate referral to secondary care or other services. Results: The analysis included 56 patients, 21 men and 35 women, with a median age of 86 years. Seventeen patients who had significantly deranged blood test results were transferred to hospital, as were another 10 who did not have such results; 27 patients were admitted in total. Twenty-nine patients remained in their usual environment; of these, four presented to hospital within the next 30 days, and no deaths or adverse events were reported. Conclusion: Point-of-care testing by the ambulance services is feasible and, when combined with telephone advice and decision support from secondary care physicians, may be effective in reducing hospital admission for frail patients in supportive care environments. Larger systematic evaluations are warranted to establish the utility and cost-effectiveness of point-of-care testing by ambulance services.